Social Science: Caring for Children in Young Family Due to Pregnant Outside Marriage - al Asy ari, M. Khoirul Hadi; Rahman, Muhammad (Proceeding International Conference on Science and Engineering, 2020)
Writing this paper aims to determine the function and influence of the family on a child, young families as a result of marride will be accidentally influenced by child care, where ideal care will be seen at the time of loyalty, attention and attention of parents to children in order to grow into a better generation. However, being too young to get married will hamper the knowledge of young couples about ideal parenting. The purpose of this study is to describe the knowledge of parenting in young families, to describe the problems of childcare and to describe the forms of care for young families as a result of accidental marriage. This research was conducted with a qualitative approach. The results of this study are the lack of knowledge about ideal parenting, so that parenting has changed the function of young families into their grandmothers or sisters. Care for young families with problems is seen from three factors: parenting, actors playing and the obstacles faced while having children. There are four forms of parenting namely democratic parenting, authoritarian parenting, permissive parenting and parenting style. Different parents will apply different parenting styles as well. However, the mayor of a young family uses democratic nurturing because they prioritize the importance of children but remain under the supervision of parents, parents are more rational, realistic, open, and able to communicate well with children. Democratic parenting style is mainly used to produce characteristics of children who are independent, obedient, honest, good communication and cooperative with others. There are several important questions in this paper, first. What is the ideal childcare method. Second. What is the impact of parents' lack of attention on a child. Third. How is the solution to bring together families who are broken home. Interview, data collection, and documentation methods are used in this paper to obtain maximum and concrete results. So that this paper can be used as a solution for families who are experiencing problems both internally and externally.